COVID-19 patients presenting with gangrenous acalculous cholecystitis: Report of two cases. (April 2022) - Hajebi, Reza; Habibi, Pedram; Maroufi, Seyed Farzad; Bahreini, Maryam; Miratashi Yazdi, Seyed Amir
Abstract: Introduction and importance: COVID-19 virus is thought to complicate underlying conditions, including acalculous cholecystitis . Two COVID-19 patients with gangrenous gallbladder are reported who were not involved with severe pneumonia. Case presentation: We present two non-critically ill patients with COVID-19 presenting with acalculous cholecystitis. Both patients had gangrenous gallbladder and had to undergo cholecystectomy. Upon surgery, one of the patients showed patchy gangrene on gallbladder and the other, a fully gangrenous gallbladder. Conclusion: There may be a possibility for COVID-19 patients with cholecystitis to develop ischemic gallbladder.